"Doctor and pharmacy shopping": A fading signal for prescription opioid use monitoring?. (1st April 2021) - Delcher, Chris; Harris, Daniel R.; Park, Changwe; Strickler, Gail K.; Talbert, Jeffery; Freeman, Patricia R.
Highlights: "Doctor or pharmacy shopping" for opioids has declined precipitously in the United States. Common data-driven algorithms may inadvertently identify patients with cancer. Multiple provider episodes may signal problems with care rather than opioid abuse. Improved methods of monitoring multiple provider episodes are needed. Abstract: Background: The term "doctor and pharmacy shopping" colloquially describes patients with high multiple provider episodes (MPEs)-a threshold count of distinct prescribers and/or pharmacies involved in prescription fulfillment. Opioid-related MPEs are implicated in the global opioid crisis and heavily monitored by government databases such as U.S. state prescription drug monitoring programs (PDMPs). We applied a widely-used MPE definition to examine U.S. trends from a large, commercially-insured population from 2010 to 2017. Further, we examined the proportion of enrollees identified as "doctor shoppers" with evidence of a cancer diagnosis to examine the risk of false positives. Methods: Using a large, commercially-insured population, we identified patients with opioid-related MPEs: opioid prescriptions (Schedule II-V, no buprenorphine) filled from ≥5 prescribers AND ≥ 5 pharmacies within the past 90 days ("5x5x90d"). Quarterly rates per 100, 000 enrollees (two specifications) were calculated between 2010 and 2017. We examined the trend in a recently published all-payer, 7 state cohort from the U.S. Centers for Disease Control and Prevention for comparison. Cancer-related ICD-9/10-CM codes were used. Results: Quarterly MPE rates declined by approximately 73 % from 18.2–4.9 per 100, 000 enrollee population with controlled substance prescriptions. In 2017, nearly one fifth of these commercially-insured enrollees identified by the 5x5x90d algorithm were diagnosed with cancer. Approximately 8% of this sample included patients with ≥ 1 buprenorphine prescriptions. Conclusions: Opioid "shopping" flags are a long-standing but rapidly fading PDMP signal. To avoid unintended consequences, such as identifying legitimate medical encounters requiring high healthcare utilization or opioid treatment, while maintaining vigilance, more nuanced and sophisticated approaches are needed.